The adverse effect of a high energy dense diet on cardiac tissue - Novelli, E. L B; Fernandes, A. A H; Campos, K. E.; Diniz, Y. S. [UNESP]; Almeida, J. A.; Faine, L. A.; Ribas, B. O. (Taylor & Francis, 2002)
Purpose: To determine whether a high energy dense diet intake increases oxidative stress and alters antioxidant enzymes in cardiac tissue. Design: A randomized, controlled study. Ninety-day-old female rats were randomly divided into two groups: one fed with a low energy dense diet (LE; 3.0 kcal g-1) and one with a high energy dense diet (HE; 4.5 kcal g-1). Materials and Methods: After 8 weeks of treatment, the animals were fasted overnight and sacrificed by decapitation. The serum was used for glucose, triacylglycerol, cholesterol, low-density lipoprotein (LDL)-cholesterol and high-density lipoprotein (HDL)-cholesterol determinations. The glycogen, lipoperoxide, lipid hydroperoxide, superoxide dismutase, glutathione peroxidase, lactate dehydrogenase, citrate synthase, total and non-protein sulphhydryl groups were determined in cardiac tissue. Results: HE decreased the myocardial glycogen content and increased the lactate dehydrogenase/citrate synthase ratio, indicating an increased glycolytic pathway and a shift from myocardial aerobic metabolism. HE-treated female rats showed increased lipoperoxide and hydroperoxide levels in cardiac tissue. Although no alterations were observed in the total sulphhydryl group and superoxide dismutase activities, glutathione peroxidase and the non-protein sulphhydryl group were significantly decreased in HE-treated animals. Conclusions: Although no alterations were observed in energy intake, HE induced an increased intake of fat and carbohydrate and an increased rate of weight gain. HE intake induced alterations in markers of oxidative stress in cardiac tissue. Hydrogen peroxide is an important toxic intermediate in the development of cardiac oxidative stress by HE. The specific nutrient content, such as fat and carbohydrate, rather than caloric intake, appears to be the main process inducing oxidative stress in HE-treated female rats.
Keywords: Cardiac tissue; High energy dense diet; Oxidative stress; Serum lipids; cholesterol; citrate synthase; glucose; glutathione peroxidase; glycogen; high density lipoprotein; hydrogen peroxide; lactate dehydrogenase; lipid hydroperoxide; lipid peroxide; low density lipoprotein; superoxide dismutase; triacylglycerol; animal experiment; animal tissue; caloric intake; carbohydrate diet; cholesterol blood level; controlled study; female; glucose blood level; heart; lipid diet; lipoprotein blood level; nonhuman; oxidative stress; priority journal; rat; triacylglycerol blood level; weight gain; Animalia